Chlamydia pneumoniae Induces Interferon Gamma Responses in Peripheral Blood Mononuclear Cells in Children with Allergic Asthma. (July 2017) - Smith‐Norowitz, T. A.; Weaver, D.; Chorny, V.; Norowitz, Y. M.; Lent, D.; Hammerschlag, M. R.; Joks, R.; Kohlhoff, S.
Abstract: Respiratory infections caused by Chlamydia pneumoniae have been associated with exacerbations of asthma. Cell‐mediated immunity (CMI) is critical for maintaining immunity. We compared interferon (IFN)‐ γ responses in C. pneumoniae ‐infected peripheral blood mononuclear cells (PBMC) in paediatric patients ± asthma. Presence of C. pneumoniae was tested from asthma patients (N = 17) and non‐asthmatic controls ( N  = 16) (PCR). PBMC were infected for 1 h ± C. pneumoniae AR‐39 (MOI = 0.1) and cultured for 48 h. IFN‐ γ levels were measured in supernatants (ELISA). C. pneumoniae ‐IgG antibodies in serum were determined (MIF). All subjects tested negative for C. pneumoniae (PCR). C. pneumoniae ‐induced IFN‐ γ production in vitro was more prevalent in asthma compared with non‐asthma; levels of IFN‐ γ were higher in asthma compared with non‐asthma ( P  =   0.003). There was no association between recent respiratory infection and positive IFN‐ γ responses. These data show that C. pneumoniae modulates IFN‐ γ responses in patients with asthma, even in absence of active infection.